2008
DOI: 10.2310/6670.2008.00033
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the Aortic Neck with a Balloon-Expandable Stent Graft in Patients with Complicated Neck Morphology

Abstract: Graft migration and other device-related problems are more frequent in abdominal aortic aneurysm (AAA) patients with a complicated neck. We wanted to evaluate the performance of a balloon-expandable stent graft in these cases. Complicated aortic neck morphology was defined as a combination of short (<15 mm) and angulated (>45 degrees) necks with or without circumferential thrombus. Severe aortic angulation was defined as less than 120 degrees. During a 24-month period, 18 consecutive patients with complicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…[24][25][26] Other investigators have used endografts able to sit onto the aortic bifurcation to address difficulties in proximal fixation. 27,28 Laparoscopic techniques have seldom been advocated and when used were generally in the setting of late neck dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Other investigators have used endografts able to sit onto the aortic bifurcation to address difficulties in proximal fixation. 27,28 Laparoscopic techniques have seldom been advocated and when used were generally in the setting of late neck dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, type II endoleaks were identified in two patients but no type I endoleak developed during 5 months of follow-up. Kolvenbach et al 16) also used a similar technique with a balloon-expandable cuff, which was inserted prior to the main body insertion to remodel the neck for 2 out of 18 in their study population all having complicated neck morphology. In their mean 11.5 months of follow-up, neither neck dilatation nor migration of stent graft was observed.…”
Section: Discussionmentioning
confidence: 99%
“…17 Similar results were observed with the VI-Datascope graft in a small series of patients with difficult neck anatomy at an average follow-up period of 11 months. 18 There are, however, two notable factors that may confound these conclusions. Generally, BES are only oversized by 5%, whereas SES are oversized by 10 to 20%.…”
Section: Can Aortic Neck Dilatation Be Prevented?mentioning
confidence: 99%